Sprache und Kognition Ereigniskonzeptualisierung im Deutschen und Tschechischen - Mertins, Barbara (Konvergenz und Divergenz, 2018)
Is our thinking and thus the worldview the same or language-specific for all people? This book is an unequivocal answer to this age-old question, which was already pursued by Wilhelm von Humboldt: Our worldview is characterized by the grammar of one's mother tongue (s), so that people perceive, verbalise and also remember events in a language-specific way. These basic insights are made possible for the first time by the experimental approach of psycholinguistic methods (such as eye-tracking) selected here. The influence of language on cognition also proves to be extremely relevant to language contact. As a result of the centuries-long language contact between German and Czech, the aspect system of Czech has changed in such a way that event conzeptualization proceeds both in Czech and in German, and that Czech is systematically different from other East and West Slavic languages.